Application of Design of Experiments to Reducing Defects in Tablet Packing Process - Maneerat, Tiwanan; Ngaoprasertwong , Jeirapat (Srinakharinwirot University Engineering Journal, 2023)
This research aimed to reduce the proportion of aluminum foil packaging in strip packs due to incomplete sealing. Including reducing the time for adjusting the machine start by analyzing the cause of the problem and related factors with the cause and effect diagram. Furthermore, screening factors using cause and effect matrix scores and Failure Mode and Effect Analysis (FMEA). Then, one factor at a time experiments were performed. Factorial experimental design principles were used to find optimal factor levels. The experiment found that the optimum factor was the temperature of the sealing roller was 130 0C, the sealing roller rotation speed was 14 rpm, and the tension of both sides of the foil was level 7. When taking the factor level obtained adapted to the tablet strip packing process, it was found that the proportion of defects in aluminum foil strips packaging that had seal defects decreased from 4.82% to 1.38%. In addition, the machine adjustment time was reduced from 130 minutes/day to 78 minutes/day.